Rural Electrification - World Bank. (Washington: World Bank, 1975)
This report discusses three main topics: (1) the prospects for successful investment in rural electrification; (2) approaches to investment from the point of view of economic justification, identification, and preparation of projects, finance, technical problems, and institutional problems; and (3) implications for the world Bank's policy and procedures. It further indicates that there is plenty of scope for successful investments in rural electrification, provided that they are properly selected and prepared. It also outlines an approach for undertaking such investments.
ne 2/05/2018
Loan
Keywords: Rural Electrification